From perceptions to beliefs: the mediating role of attitudes in pre-service English teacher cognition of Communicative Language Teaching in China - Zhou, Jingyao; Liu, Dong (Frontiers in Psychology, 2026)
IntroductionAlthough Communicative Language Teaching (CLT) has gained global endorsement, its adoption in exam-oriented EFL contexts like China is inconsistent. While prior studies emphasize in-service teachers, limited research explores pre-service teachers, whose cognitions will influence future language pedagogy. This study investigates how pre-service English teachers’ perceptions of secondary school classrooms shape their attitudes toward grammar- versus communication-focused instruction, and subsequently their beliefs about language learning, with attitudes as a mediator. It also examines how this interrelation differs by gender and English learning starting age.MethodsBased on a large-scale survey (n = 865) of English majors in China, data were analyzed via descriptive statistics, t-tests, exploratory and confirmatory factor analyses, and structural equation modeling (SEM).ResultsFindings reveal dominant grammar-focused perceptions, yet stronger attitudes favoring communicative approaches. SEM results confirm perceptions indirectly influence beliefs through attitudes, underscoring attitudes’ mediating role in teacher cognition. Subgroup analyses show variations, with females and early starters exhibiting stronger communicative orientations.DiscussionThese insights highlight the enduring belief-practice gap in high-stakes environments and advocate for teacher training, curriculum reforms, localized CLT adaptations, and AI integration (such as through personalized simulations and real-time feedback) to foster communicative practices and bridge preparation deficiencies.